+0  
 
+2
110
2
avatar

e^(xy) + y^2 = sin(x + y)

Guest Mar 20, 2017
Sort: 

2+0 Answers

 #1
avatar
0

e^(xy) + y^2 = sin(x + y)

 

Answer:

 

(y^2)+(e^(x*y))

Guest Mar 20, 2017
 #2
avatar+6900 
0

Assume that y is a imaginary number, y = ai

e^(axi) - a^2 = sin(x + ai)

cos(ax) + i sin(ax) - a^2 = sin x cosh a + i cos a sinh b

 

This seems not solvable :(

MaxWong  Mar 23, 2017

10 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details